Growth Performance of Cyprinus carpio Fry using Free Lysine Incorporated Feed in Aquarium - Lamsal, Ram Kumar; Gurung, Shailesh; Mandal, Ram Bhajan; Shah, Shambhu (Journal of Agriculture and Resource Management, 2024)
A 90-day experiment was conducted at the Institute of Agriculture and Animal Science, Paklihawa, Nepal to assess the early growth response of common carp (Cyprinus carpio L. var. communis) at varying levels of free lysine supplemented diets in glass aquaria. The basal diet comprised a mixture of rice bran, wheat bran, mustard oilcake, and soybean meal (T0). Three other treatments included basal diet along with 0.08% free lysine (T1), 0.16% free lysine (T2), and 0.24% free lysine (T3). A completely randomized design (CRD) was employed with four treatments replicated three times. Advanced fry of common carp approximately 1.4 g size were stocked in 1x2x1 cubic feet aquariums with a 45-liters water capacity at the rate of 10 fish per aquarium. Locally prepared pellet feed, maintained with 30% crude protein based on different experimental diets, were supplied at 5% of wet body weight of fish with feed adjusted fortnightly. At harvest, fry fed with lysine supplemented diets (T2 and T3) exhibited relatively better growth in mean final weight, mean weight gain, mean daily weight gain, specific growth and feed conversion ratio compared to the control (T0) and treatment T1. T2 achieved the highest weight gain of 4.56±0.07g followed by T3(3.75±0.21 g) and T1 (3.52±0.31 g), while control (T0) achieved the lowest weight gain of 3.17±0.11 g. Treatment T2 proved to be most effective, showing the highest weight gain, daily weight gain, low FCR and high SGR. Water parameters (temperature, dissolved oxygen, pH, ammonia, nitrate, phosphorous, and chloride) remained stable throughout the study.